Exploring Cognitive Task Found in English Textbook “English for Nusantara” - Rizal Wahid Permana Putra; Hasanah, Uswatun; Mustofa, Mutmainnah (Universitas Cokroaminoto Palopo, 2025)
English for Nusantara is an English textbook used by the Junior high school students in regarding to the implementation of Merdeka curriculum in Indonesia. Further, it is vital to use the English textbook by considering the specific tasks to engage students’ activities effectively. This research aims at analysing task types found in English for Nusantara textbook. This research is a content analysis using a descriptive mixed approach. The data is collected through document analysis including task descriptions, task types, and instruction given, and analysed through Nunan’s framework (1999). The findings indicated that there were 51 tasks used. There were predicting, classifying, inducing, concept-mapping, interferencing, and discriminating. In addition, the most frequent tasks employed in English for Nusantara textbook was interferencing tasks. In short, based on the result of data analysis, still, it showed that there was imbalanced of task distribution in five chapter of English for Nusantara textbook